How Do the Constructs of the TPACK Framework Relate with Use of ICT in Pedagogy among Teachers of Mathematical Disciplines in Universities in Uganda? - Batiibwe, Marjorie S. K .; K, Fred E. (African Journal of Education,Science and Technology (AJEST), 2018)
This study sought to establish the relationship between use of ICT in pedagogy (UIP) and knowledge among teachers of mathematical disciplines in universities in Uganda. Knowledge was conceptualized according to the Technological Pedagogical Content Knowledge (TPACK) framework as having seven constructs, namely content knowledge (CK); pedagogical knowledge (PK); technological knowledge (TK); pedagogical content knowledge (PCK); technological pedagogical knowledge (TPK); technological content knowledge (TCK); and technological pedagogical content knowledge (TPACK). Data were collected from 261 respondents using a questionnaire, and analysed using factor analysis, Cronbach alpha, means and multiple regression. Means indicated that while the respondents rated themselves as only fair on UIP, they rated themselves high on pedagogical and content knowledge constructs (PCK, CK & PK) and low on technology knowledge constructs (TPACK, TPK, TK & TCK). Regression revealed that apart from the TPACK construct, none of the other six knowledge constructs was a significant correlate of UIP. It was concluded that in order to use ICT in pedagogy, teachers need TPACK in its entirety and not its constituents. It was thus recommended that when training teachers for UIP, the respective stakeholders in the various universities should ensure that the training is wholesome on content, pedagogy and technology.